DIRECTIVE SPEECH ACTS IN THE MOVIE “BIG HERO 6” - Utari Swiyandara; Irfan Hamonangan Tarihoran (STKIP Paracendekia NW Sumbawa, 2023)
Pragmatics is a branch of linguistics that is interesting for writers to study more deeply. This study aims to explaining the classification of forms and types of directive speech acts in Big Hero 6 and to understand the implied meaning of each speech among players. The subjects of this research are all utterances in the Big Hero 6. The object of this research is all utterances which are directive speech acts in Don Hall's Big Hero 6. The data in this study are in the form of phrases or sentences that contain directive speech acts in the Big Hero 6. Data are collected by use of documentation method and library study. Data analysis is performed using pragmatic matching method. The analysis of the types of directive speech acts is carried out using the speaking component as a determining tool. This research applies descriptive qualitative method. Based on the findings, the form of directive speech acts totaling 96 data, are identified, i.e. i) questions (46 data); ii) orders (25 data); (iii) giving permission (1 datum); (iv) prohibition (15 data); asking (3 data); suggesting (4 data); and warning (2 data) with interrogative types (46 data), imperative (42 data) and declarative (8 data). Then, it can be concluded that the dominant directive is interrogative form.